Simulation of plasmons on a metal nano-ring. Issue 1 (February 2021) - Kozlova, E S; Kotlyar, V V
Abstract: Using the finite difference time domain method, it is shown that a laser beam with a wavelength of 633 nm and circular polarization forms on the silver nano-ring with a width of 260 nm a surface plasmon polariton with a full width at half maximum of 0.25λ, and the maximum intensity of 1.873 a. u.